A Study of Occupational Stress and Mental Health of Working Women: Examining the Impact of Occupational Stress on Mental Health in Working Women (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Themain aim of the present study was to analyzed and find out the relationshipbetween occupational stress and mental health among working women. Four hundredfifty working women as a teacher, nurse and clerk participated in study.Standardized Occupational Stress Index by Shrivastav and Mental HealthInventory by Jagdish were used for data collection. To analyze the data‘t’ testand (product moment) correlation technique were used. Results indicate thathigh occupational stress was found among nurses in comparison to clerks andteachers. Significant correlation found between occupation stress and mentalhealth among working women.